Assistance in the Creation of Google My Business to Increase Sales Revenue - Murdiawati, Dewi; Sihotang, Ellen Theresia (Bubungan Tinggi: Jurnal Pengabdian Masyarakat, 2024)
The progress of technology and the COVID-19 pandemic have brought changes to various industrial sectors, including the Micro, Small, and Medium Enterprises (MSME) sector. Both conditions have led several MSMEs to revamp their strategies in various functions, including marketing strategies shifting towards digital platforms. One MSME impacted by the COVID-19 pandemic experienced a nearly 92% decline in revenue and has not yet fully recovered even in the post-COVID-19 period. Based on these challenges, this Community Service (PkM) activity aimed to implement digital marketing strategies using Google My Business to increase revenue by at least 20%. The method employed was Participation Action Research (PAR), which began with the initial stages of surveying and observing partners, followed by problem formulation and solution development. The second stage involved assisting partners in creating their Google My Business profiles, and it concluded with an evaluation in the third stage. The direct evaluation showed that the partners could effectively operate Google My Business with its available features. The partners responded positively, providing favourable ratings through the questionnaire, indicating they gained knowledge about digital marketing. The Community Service activity implies that the partners can now be more easily found by potential customers and interact through review and response features, ultimately leading to increased sales revenue. The partners hoped that future Community Service activities related to digital marketing could continue, possibly exploring other social media platforms as additional digital marketing channels.